Posted by **John** on Friday, December 27, 2013 at 7:24pm.

f(x)=13x^2 -15x-14

g(x)=15x^3+14x^2-15x+12

find f(3) × f(10) + f(-7) × g(9)

## Answer this Question

## Related Questions

- Math - f(x)=13x^2 -15x-14 g(x)=15x^3+14x^2-15x+12 find f(3) × f(10) + f(-7) × g(...
- Algebra - I need help trying to put the correct vocabulary words when solving ...
- Algebra - I need help trying to put the correct vocabulary words when solving ...
- math - Solve by elimination 5x+y=2 3x+y=1 This is what I got : 3(5x+y=2) -5(3x+y...
- algebra - -15(3+x)=-6x-9 -45-15x=-6x-9 -45-15x+15x=-6x+-15x-9 -45=21x-9 -45=x-9...
- algbrea - 3x-5(3x-7)= 2(x+9) + 45 3x-15x+35= 2x+18 +45 -12x + 35 = 2x+63 -12x -...
- Math - William solves the equation 5(3x-2)=15x-2. How many solutions does he ...
- math - if y=5x-2, then -3x=? PLEASE EXPLAIN a 5x -6 b 15x-6 c 15x+6 d -15-6 e -...
- Algebra 1b! - 1. Find the excluded value of x for the polynomomial expression ...
- Math - A stunt pilot is testing a new plane. The equation that models his height...